Two-step synthesis method and material of silicon-containing low-saturation high-dielectric-constant microwave ferrite
By using Si4+ substitution and Al3+ and Gd3+ substitution methods in microwave ferrite materials, combined with two-step synthesis processes, the problem of difficult materials in the prior art to take into account low saturation, low temperature coefficient and high dielectric constant performance, and realizes the High performance material preparation suitable for miniaturized ferrite devices.
Patent Information
- Application Number
- CN202411821874.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to take into account the performance indicators of low saturation, low temperature coefficient and high dielectric constant, and limits the miniaturization and engineering applications of S-band, L-band and P-band ferrite devices.
Si4+ is used to reduce the saturation magnetization of the material at the d position, and the temperature coefficient and dielectric constant of the material are replaced by Al3+ and Gd3+. Combined with a two-step synthesis process, a low saturation, low temperature coefficient and high dielectric constant are prepared. Performance microwave ferrite material.
The low saturation magnetization strength of the material (4πMS≤900Gs), low temperature coefficient (≤3‰/℃) and high dielectric constant (εr≥20) are achieved, and the miniaturized S-band, L-band, and P-band ferrite is met. Device requirements.
Smart Images

Figure CN119430901A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microwave ferrite materials, and in particular relates to a two-step synthesis method and material of silicon-containing low-saturation high-dielectric constant microwave ferrite. Background Art
[0002] The development of high dielectric constant microwave ferrite materials is an important technical direction for miniaturization of ferrite devices. Among them, ferrite devices working in the S-band, L-band, and P-band have larger relative size and weight, and face more urgent miniaturization needs. It is urgent to develop high dielectric constant microwave ferrite materials with low saturation magnetization.
[0003] At present, there are relatively few patents on low saturation high dielectric constant microwave ferrite materials. CN106242547, CN112456998, and CN116813321 disclose low saturation high dielectric constant ferrites with partial saturation magnetization less than 1000Gs and relative dielectric constant greater than 20, but the Curie temperature of these materials is low or not reported, which directly affects the engineering application of the materials. CN113896521 discloses a low saturation high Curie temperature high dielectric constant ferrite material. According to its chemical formula, Gd 3+ The substitution amount is less than 0.6, which indicates that the temperature coefficient of saturation magnetization is large, which restricts its engineering application. The large temperature coefficient has always been the main reason why low-saturation high-dielectric constant ferrite materials have not been put into practical use. On the one hand, it leads to the deterioration of the temperature stability of the electrical performance of ferrite devices within their operating temperature range (-55℃~+85℃ or -40℃~+120℃); on the other hand, it limits the power handling capacity of ferrite devices, because the high power heating of the device makes the deterioration of its electrical performance more significant.
[0004] Therefore, high dielectric constant ferrite materials for miniaturized applications in S-band, L-band, and P-band ferrite devices urgently need to solve the technical problem that it is difficult to balance the performance indicators of low saturation, low temperature coefficient, and high dielectric constant. Summary of the invention
[0005] One of the purposes of the present invention is to provide a microwave ferrite material with low saturation magnetization, low temperature coefficient and high dielectric constant to solve the above technical problems.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: a silicon-containing low saturation high dielectric constant microwave ferrite material, whose chemical formula is Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe(5-c-d-e-δ) O 12 , where 0.9≤a≤2.0, 0.6≤b≤1.2, 0.2≤c≤0.8, 0≤d≤0.6, 0≤e≤0.6, 0.03≤δ≤0.1, δ is the amount of iron deficiency.
[0007] The more mature BiCaV formulation system currently uses V in the garnet lattice oxygen tetrahedral position (d position) 5+ Substitution is used to reduce the saturation magnetization of the material. Bi is used in the garnet lattice oxygen dodecahedron position (c position) 3+ Substitution to increase the dielectric constant of the material while balancing the electrical charge to a V 5+ Substitution requires 2 Ca groups at the c position 2+ To reduce the saturation magnetization of the material, d is V 5+ The amount of substitution has increased significantly, and at the same time, in order to balance the electricity price, the c position Ca 2+ The amount of substitution needs to be doubled accordingly, but the Gd that regulates the material temperature coefficient 3+ , dielectric constant Bi 3+ , peak power Dy 3+ Plasma substitution requires the c position, and the limited number of c positions makes it difficult for the BiCaV formulation system to take into account the low saturation, low temperature coefficient, and high dielectric constant performance indicators. 4+ Substitution to reduce the saturation magnetization of the material, 1 Si 4+ Substitution requires only one Ca at the c position 2+ Replacement is used to balance electricity prices, and some c positions are saved to regulate the temperature coefficient, dielectric constant, and peak power of the material, so that ferrite materials with low saturation, low temperature coefficient, and high dielectric constant performance indicators can be prepared, which can meet the needs of miniaturized S-band, L-band, and P-band ferrite devices for low saturation and high dielectric constant microwave ferrite materials.
[0008] The present invention adopts Si 4+ Substitution reduces the saturation magnetization of the material by Al 3+ , Gd 3+ Replace the saturation magnetization intensity and temperature coefficient of the regulating material; use highly polarized ion Bi 3+ Replacement, improve the dielectric constant of the material; through the appropriate amount of In 3+ Doping reduces the ferromagnetic resonance linewidth of the material; an appropriate amount of iron deficiency suppresses the dielectric loss of the material.
[0009] A second object of the present invention is to provide a two-step synthesis method of the above-mentioned silicon-containing low saturation high dielectric constant microwave ferrite, comprising the following steps:
[0010] (1) Ingredients, according to the chemical formula Bi a Gb Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where 0.9≤a≤2.0, 0.6≤b≤1.2, 0.2≤c≤0.8, 0≤d≤0.6, 0≤e≤0.6, 0.03≤δ≤0.1, δ is the iron deficiency, calculate and weigh each raw material.
[0011] (2) mixing, mixing the raw materials weighed in step (1) to obtain a mixed powder;
[0012] (3) pre-calcining, pre-calcining the mixed powder obtained in step (2) at a temperature of 870° C. to 950° C. for 4 to 8 hours to obtain a pre-calcined material;
[0013] (4) ball milling, wet ball milling and drying the pre-burned material obtained in step (3) to obtain a secondary material;
[0014] (5) granulation, mixing the secondary material obtained in step (4) with a binder and granulating the mixture to obtain a granular material;
[0015] (6) forming, pressing the granular material obtained in step (5) to obtain a green body;
[0016] (7) Sintering: sintering the green body obtained in step (6) at a sintering temperature of 900° C. to 980° C. for more than 20 hours.
[0017] Preferably, the pre-calcination in step (3) is a two-step synthesis process, specifically comprising: the first step of rapidly heating from room temperature to 770°C to 830°C and keeping the temperature for more than 20 hours, and keeping the temperature at 770°C to 830°C for a long time to make Bi with a larger ionic radius 3+ Through the perovskite phase and with the phase transformation into the garnet main phase, the impurity phase bismuthite phase Bi 25 FeO 39 The ferromagnetic resonance line width of the ferrite material is suppressed; the second step is to continue to heat up to the pre-sintering temperature of 870℃~950℃ and keep it for 4~8h to promote In 3+ Replace completely.
[0018] Preferably, the first step of the two-step synthesis process in step (3) is to rapidly heat the temperature from room temperature to 770°C to 830°C at a rate of not less than 6°C / min. By rapidly heating, the impurity phase Bi2O3 is suppressed. 25 FeO 39 , the formation of mullite phase Bi2Fe4O9 in the low temperature range, thereby further reducing the ferromagnetic resonance linewidth of the ferrite material.
[0019] Preferably, the raw materials described in step (1) are Bi2O3, Gd2O3, CaCO3, Y2O3, SiO2, Al(OH)3, In2O3, Fe2O3, and their purity is analytical grade.
[0020] Preferably, in step (2), mixing is performed by wet ball milling, the medium is deionized water, pure water or ethanol, the balls are zirconium oxide or steel balls, the ratio of material: ball: water is 1:3-4:1-2, and the ball milling time is 16-32 hours.
[0021] Preferably, in step (4), the ball milling medium is deionized water, pure water or ethanol, the ball is zirconium oxide or steel ball, the ratio of material: ball: water is 1:3-4:0.8-1.5, and the ball milling time is 16-32 hours.
[0022] Preferably, the adhesive in step (5) is a polyvinyl alcohol aqueous solution with a concentration of 6wt% to 10wt%.
[0023] Preferably, the relative density of the green body obtained by compression molding in step (6) is not less than 60%.
[0024] The third object of the present invention is to provide the application of the above silicon-containing low saturation high dielectric constant microwave ferrite material in miniaturized S-band, L-band and P-band ferrite devices.
[0025] Compared with the prior art solutions, the present invention has the following beneficial effects:
[0026] (1) Formula design using Si 4+ Substitution reduces the saturation magnetization of the material, Al 3+ , Gd 3+ 、Bi 3+ 、In 3+ The saturation magnetization intensity and temperature coefficient, ferromagnetic resonance line width and dielectric constant of the material are jointly substituted and regulated, solving the technical problem that the material is difficult to balance the performance indicators of low saturation, low temperature coefficient and high dielectric constant. The prepared microwave ferrite material has a saturation magnetization intensity of 4πM S ≤900Gs, temperature coefficient of saturation magnetization ≤3‰ / ℃ (20℃~80℃), relative dielectric constant ε r ≥20, which can meet the needs of miniaturized S-band, L-band, and P-band ferrite devices for low saturation and high dielectric constant microwave ferrite materials.
[0027] (2) The preparation method adopts a two-step synthesis process to effectively reduce the ferromagnetic resonance line width of the silicon-containing low saturation high dielectric constant microwave ferrite material. By keeping the temperature at 770℃~830℃ for a long time, Bi 3+Entering the garnet main phase through the perovskite phase, the impurity phase bismuthite phase Bi 25 FeO 39 The ferromagnetic resonance line width of the material is effectively reduced by being suppressed; and the mixed phase Bi phase is suppressed by rapidly heating up at a low temperature range of 770℃ to 830℃. 25 FeO 39 , mullite phase Bi2Fe4O9, thereby further reducing the ferromagnetic resonance linewidth of the material.
[0028] (3) Avoid using toxic raw material V2O5, which is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM photo of the ferrite material obtained in Example 1 of the present invention;
[0030] Figure 2 This is the XRD spectrum of the ferrite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the accompanying drawings.
[0032] Embodiment 1:
[0033] A microwave ferrite material with low saturation, low temperature coefficient and high dielectric constant, whose chemical formula is: Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=1.4, b=1.1, c=0.5, d=0, e=0.5, δ=0.05;
[0034] The preparation method is as follows:
[0035] (1) Ingredients, according to the chemical formula Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=1.4, b=1.1, c=0.5, d=0, e=0.5, δ=0.05, calculate and weigh each raw material, the raw materials are Bi2O3, Gd2O3, CaCO3, Y2O3, SiO2, In2O3, Fe2O3, and the purity of the raw materials is analytical grade;
[0036] (2) mixing, adding a certain proportion of the raw materials weighed in step (1) into deionized water and mixing and ball milling at a ball milling speed of 60 to 80 r / min, and drying and sieving after ball milling for 24 hours to obtain a mixed powder;
[0037] (3) pre-calcining, pre-calcining the mixed powder obtained in step (2), heating from room temperature to 820° C. at a rate of 6° C. / min, keeping the temperature for 20 h, then heating to the pre-calcining temperature of 880° C., keeping the temperature for 4 h, to obtain a pre-calcined material;
[0038] (4) ball milling: adding a certain proportion of deionized water to the pre-burned material obtained in step (3) for wet ball milling at a speed of 60 to 80 r / min. After ball milling for 24 hours, drying and sieving are performed to obtain secondary material;
[0039] (5) granulation, adding an 8 wt % polyvinyl alcohol aqueous solution to the secondary material obtained in step (4), mixing evenly and granulating to obtain a granular material;
[0040] (6) forming, pressing the granular material obtained in step (5) to obtain a green body;
[0041] (7) Sintering: sinter the green body obtained in step (6) at a sintering temperature of 930° C. for more than 20 hours.
[0042] The electromagnetic properties of the obtained material are shown in Table 1, and the SEM photo of the material cross section is shown in the attached figure. Figure 1 The XRD spectrum of the material phase analysis is shown in the attached Figure 2 shown.
[0043] Embodiment 2:
[0044] A microwave ferrite material with low saturation, low temperature coefficient and high dielectric constant, whose chemical formula is: Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=1.4, b=1.1, c=0.3, d=0.2, e=0.5, δ=0.05;
[0045] The preparation method is as follows:
[0046] (1) Ingredients, according to the chemical formula Bi a G b Ca c Y (3-a-b-c) Si c Al dIn e Fe (5-c-d-e-δ) O 12 , where a=1.4, b=1.1, c=0.3, d=0.2, e=0.5, δ=0.05, calculate and weigh each raw material, the raw materials are Bi2O3, Gd2O3, CaCO3, Y2O3, SiO2, Al(OH)3, In2O3, Fe2O3, and the purity of the raw materials is analytical grade;
[0047] (2) mixing, adding a certain proportion of the raw materials weighed in step (1) into deionized water and mixing and ball milling at a ball milling speed of 60 to 80 r / min, and drying and sieving after ball milling for 24 hours to obtain a mixed powder;
[0048] (3) pre-calcining, pre-calcining the mixed powder obtained in step (2), heating from room temperature to 820° C. at a rate of 6° C. / min, keeping the temperature for 20 h, then heating to the pre-calcining temperature of 880° C., keeping the temperature for 4 h, to obtain a pre-calcined material;
[0049] (4) ball milling: adding a certain proportion of deionized water to the pre-burned material obtained in step (3) for wet ball milling at a speed of 60 to 80 r / min. After ball milling for 24 hours, drying and sieving are performed to obtain secondary material;
[0050] (5) granulation, adding an 8 wt % polyvinyl alcohol aqueous solution to the secondary material obtained in step (4), mixing evenly and granulating to obtain a granular material;
[0051] (6) forming, pressing the granular material obtained in step (5) to obtain a green body;
[0052] (7) Sintering: sinter the green body obtained in step (6) at a sintering temperature of 930° C. for more than 20 hours.
[0053] After testing, the electromagnetic properties of the prepared materials are shown in Table 1.
[0054] Embodiment 3:
[0055] A microwave ferrite material with low saturation, low temperature coefficient and high dielectric constant, whose chemical formula is: Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=0.9, b=0.9, c=0.7, d=0, e=0.32, δ=0.05;
[0056] The preparation method is as follows:
[0057] (1) Ingredients, according to the chemical formula Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=0.9, b=0.9, c=0.7, d=0, e=0.32, δ=0.05, calculate and weigh each raw material, the raw materials are Bi2O3, Gd2O3, CaCO3, Y2O3, SiO2, In2O3, Fe2O3, and the purity of the raw materials is analytical grade;
[0058] (2) mixing, adding a certain proportion of the raw materials weighed in step (1) into deionized water and mixing and ball milling at a ball milling speed of 60 to 80 r / min, and drying and sieving after ball milling for 24 hours to obtain a mixed powder;
[0059] (3) pre-calcining, pre-calcining the mixed powder obtained in step (2), heating from room temperature to 820° C. at a rate of 6° C. / min, keeping the temperature for 20 h, then heating to the pre-calcining temperature of 880° C., keeping the temperature for 4 h, to obtain a pre-calcined material;
[0060] (4) ball milling: adding a certain proportion of deionized water to the pre-burned material obtained in step (3) for wet ball milling at a speed of 60 to 80 r / min. After ball milling for 24 hours, drying and sieving are performed to obtain secondary material;
[0061] (5) granulation, adding an 8 wt % polyvinyl alcohol aqueous solution to the secondary material obtained in step (4), mixing evenly and granulating to obtain a granular material;
[0062] (6) forming, pressing the granular material obtained in step (5) to obtain a green body;
[0063] (7) Sintering: sinter the green body obtained in step (6) at a sintering temperature of 930° C. for more than 20 hours.
[0064] After testing, the electromagnetic properties of the prepared materials are shown in Table 1.
[0065] Embodiment 4:
[0066] A microwave ferrite material with low saturation, low temperature coefficient and high dielectric constant, whose chemical formula is: Bi a G b Ca c Y (3-a-b-c) Si c Al d Ine Fe (5-c-d-e-δ) O 12 , where a=1.6, b=0.9, c=0.5, d=0, e=0.5, δ=0.05;
[0067] The preparation method is as follows:
[0068] (1) Ingredients, according to the chemical formula Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where a=1.6, b=0.9, c=0.5, d=0, e=0.5, δ=0.05, calculate and weigh each raw material, the raw materials are Bi2O3, Gd2O3, CaCO3, Y2O3, SiO2, In2O3, Fe2O3, and the purity of the raw materials is analytical grade;
[0069] (2) mixing, adding a certain proportion of the raw materials weighed in step (1) into deionized water and mixing and ball milling at a ball milling speed of 60 to 80 r / min, and drying and sieving after ball milling for 24 hours to obtain a mixed powder;
[0070] (3) pre-calcining, pre-calcining the mixed powder obtained in step (2), heating from room temperature to 820° C. at a rate of 6° C. / min, keeping the temperature for 20 h, then heating to the pre-calcining temperature of 880° C., keeping the temperature for 4 h, to obtain a pre-calcined material;
[0071] (4) ball milling: adding a certain proportion of deionized water to the pre-burned material obtained in step (3) for wet ball milling at a speed of 60 to 80 r / min. After ball milling for 24 hours, drying and sieving are performed to obtain secondary material;
[0072] (5) granulation, adding an 8 wt % polyvinyl alcohol aqueous solution to the secondary material obtained in step (4), mixing evenly and granulating to obtain a granular material;
[0073] (6) forming, pressing the granular material obtained in step (5) to obtain a green body;
[0074] (7) Sintering: sinter the green body obtained in step (6) at a sintering temperature of 930° C. for more than 20 hours.
[0075] After testing, the electromagnetic properties of the prepared materials are shown in Table 1.
[0076] Comparative Example 1:
[0077] Compared with Example 1, the difference of this comparative example is that its chemical formula is Bi 0.9 G 1.1 Ca 1.0 V 0.5 In 0.5 Fe 3.95 O 12 The ferrite material was prepared according to the process of Example 1, with the pre-sintering temperature changed to 930°C and the sintering temperature changed to 1000°C. The electromagnetic properties of the obtained material were shown in Table 1. 5+ Replace with V 5+ Replace, for the equilibrium electricity price 1 unit V 5+ Substitution requires 2 units of Ca 2+ substitution, resulting in Ca 2+ The amount of substitution increases by 0.5. If the material temperature coefficient remains unchanged, Bi 3+ The amount of substitution must be reduced accordingly by 0.5, ultimately resulting in a decrease in the relative dielectric constant of the resulting material from 27 to 20.
[0078] Comparative Example 2:
[0079] Compared with Example 1, the difference of this comparative example is that its chemical formula is Bi 1.4 G 0.6 Ca 1.0 V 0.5 In 0.5 Fe 3.95 O 12 The ferrite material was prepared according to the process of Example 1, with the pre-sintering temperature changed to 930°C and the sintering temperature changed to 960°C. The electromagnetic properties of the obtained material were shown in Table 1. Comparative Factors: Comparative Example 1 Based on Example 1, Si 5+ Replace with V 5+ Replacement, also due to the equilibrium price leads to Ca 2+ The substitution amount increases by 0.5. If the dielectric constant of the material remains unchanged, Gd 3+ The substitution amount must be reduced by 0.5 accordingly, which ultimately leads to an increase in the saturation magnetization of the obtained material and a deterioration in the temperature coefficient.
[0080] Comparative Example 3:
[0081] Compared with Example 1, the difference of this comparative example is that the two-step synthesis process is not adopted, that is, step (3) pre-sintering is to raise the temperature from room temperature to the pre-sintering temperature of 880°C at a rate of 1-4°C / min, and keep the temperature for 4h to obtain the pre-sintered material, and the remaining steps are prepared according to the process flow of Example 1. The electromagnetic properties of the prepared materials are shown in Table 1. Comparative factor explanation: Comparative Example 1 does not adopt the two-step synthesis process on the basis of Example 1, but uses the conventional one-step synthesis process for pre-sintering instead. The ferromagnetic resonance line width of the prepared material is large, which limits its engineering application.
[0082] It should be noted that the pre-sintering temperature and sintering temperature of high dielectric constant microwave ferrite materials are closely related to their constituent elements. In order to ensure that the ferrite materials prepared in Comparative Examples 1 and 2 have a similar quality level to that of Example 1 so that electromagnetic performance can be compared, the pre-sintering temperature and sintering temperature are adjusted accordingly. On the other hand, the saturation magnetization intensity and its temperature coefficient are intrinsic parameters of the material that depend on the chemical formula composition. The dielectric constant is related to Bi 3+ The replacement amount is positively correlated, so the adjustment of pre-firing temperature and sintering temperature does not affect the contrast effect.
[0083] The materials obtained in all the embodiments and comparative examples were tested for electromagnetic properties such as saturation magnetization intensity and its temperature coefficient, ferromagnetic resonance line width, and dielectric constant. The test results are shown in Table 1.
[0084] Table 1 Electromagnetic properties of the embodiments and comparative examples
[0085]
[0086] Analysis of the above performance data:
[0087] The saturation magnetization intensity of the materials in Examples 1-3 of the present invention is 4πM S ≤900Gs, temperature coefficient of saturation magnetization ≤3‰ / ℃ (20℃~80℃), relative dielectric constant ε r ≥20, ferromagnetic resonance line width ΔH≤80Oe, with good comprehensive performance, which can meet the needs of miniaturized S-band, L-band and P-band ferrite devices for low saturation and high dielectric constant microwave ferrite materials.
[0088] The above embodiments further describe the technical solutions and beneficial effects of the present invention, but it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Any modification, equivalent substitution, improvement, etc. made by ordinary technicians in the technical field of the present invention without departing from the present concept shall be deemed to fall within the protection scope of the present invention.
Claims
1. A silicon-containing low saturation high dielectric constant microwave ferrite material, characterized in that: Its chemical formula is: Bi a G b Ca c Y (3-a-b-c) Si c Al d In e Fe (5-c-d-e-δ) O 12 , where 0.9≤a≤2.0, 0.6≤b≤1.2, 0.2≤c≤0.8, 0≤d≤0.6, 0≤e≤0.6, 0.03≤δ≤0.1, δ is the amount of iron deficiency.
2. The two-step synthesis method of a silicon-containing low saturation high dielectric constant microwave ferrite according to claim 1, characterized in that: The following steps are involved: (1) Ingredients: Calculate and weigh each raw material according to the chemical formula; (2) mixing, mixing the raw materials weighed in step (1) to obtain a mixed powder; (3) pre-calcining, pre-calcining the mixed powder obtained in step (2) at a temperature of 870° C. to 950° C. for 4 to 8 hours to obtain a pre-calcined material; (4) ball milling, wet ball milling and drying the pre-burned material obtained in step (3) to obtain a secondary material; (5) granulation, mixing the secondary material obtained in step (4) with a binder and granulating the mixture to obtain a granular material; (6) forming, pressing the granular material obtained in step (5) to obtain a green body; (7) Sintering: sintering the green body obtained in step (6) at a sintering temperature of 900° C. to 980° C. for more than 20 hours.
3. The two-step synthesis method of a silicon-containing low saturation high dielectric constant microwave ferrite according to claim 2, characterized in that: The pre-calcination in step (3) is a two-step synthesis process, specifically comprising: the first step is to rapidly heat from room temperature to 770°C to 830°C and keep the temperature for more than 20 hours to promote Bi 3+ Entering the garnet main phase through the perovskite phase to suppress the impurity phase Bi 25 FeO 39 The second step is to continue heating to the pre-burning temperature of 870℃~950℃ and keep it for 4~8h to promote In 3+ Replace completely.
4. The two-step synthesis method of a silicon-containing low saturation high dielectric constant microwave ferrite according to claim 3, characterized in that: The heating rate from room temperature to 770°C to 830°C is not less than 6°C / min to inhibit the formation of the impurity phase Bi 25 FeO 39 , mullite phase Bi2Fe4O9.
5. The silicon-containing low saturation high dielectric constant microwave ferrite material according to claim 1, characterized in that: Saturation magnetization 4πM S ≤900Gs, temperature coefficient of saturation magnetization ≤3‰ / ℃ (20℃~80℃), relative dielectric constant ε r ≥20.
Citation Information
Patent Citations
Garnet ferrite material applied to ultrahigh-power lock-type phase shifter
CN108191423A
Garnet ferrite material with high dielectric constant and medium saturation magnetization and preparation method thereof
CN116409988A
Ferrite material with low hyperfrequency losses and production method
WO2006067088A1